Prevalence study of Duchene Muscular Dystrophy and its Genetic Sequence in Southern India - Sattenapalli, Nigama Chandra; Areti, Anka Rao; Koteswara Rao, Siva Naga; Alavala, Rajasekhar Reddy; Kulandaivelu, Uma Sankar (Iranian Journal of Child Neurology, 2023)
Objective Duchene Muscular dystrophy (DMD) is the common X-linked heterogenous progressive muscular dystrophy characterized by mutations in the DMD gene. The frequency of dystrophin gene mutations is varied in different DMD population. A precise diagnosis can help to reduce the severity of DMD since it aids in planning of targeted medical treatment and required therapies. This study was aimed to investigate the mutation type, their rate and distribution of DMD’S in southern India. Materials & Methods An observational study was conducted on 250 genetically confirmed DMD patients from March,2019 to March,2021. The distribution pattern and rate of mutations (deletion, duplication, nonsense mutations, minor mutations) were investigated. Results Mutation spectrum was studied on 250 DMD patients, of which 63% exon deletion pattern were reported. 16% deletions were detected in proximal hot region (exons 3-28). The duplications were found 21% in the proximal hotspot largest region (exon 3-25). 16% of the patients reported single deletion (45 exon), 10.7% reported deletions of exon 44. Point mutations detected in 6%, small mutations were detected in 1.2%, non-sense mutations were detected in 2% of study population respectively. Missense Missense Mutations were detected in 0.8% of study population Conclusion This study estimates mutation spectrum of exon deletion pattern (63%) was predominantly identified in distal region; duplication was most frequent in proximal region. Point mutations, Nonsense mutations and small mutations have a least accountability. This study adds a real world evidence for developing research therapies in DMD